Irony Through Psychoanalysis. - Sacerdoti, Giorgio, 1925- (Karnac Books, 1992)
The title of this book, Irony Through Psychoanalysis, reveals its double register in which the psychoanalysis and irony are respectively the object and the means (or the viewpoint) or vice versa. Thus, the first chapter reviews the modern concepts of irony through the psychoanalytic lens, whilst the two central chapters examine clinical psychoanalysis and psychoanalytic theorization from the perspective of irony. Making extensive use of detailed personal material, Chapter Two looks at how the concept of irony might be broadened to include preconscious and unconscious aspects, and how we might s.